Inheritance Risk Calculation Strategic and Formulation for Genetic Diseases: a Scoping Review - Suhanda, Suhanda; Setiawan, Henri; Hidayat, Nur; Ariyanto, Heri (Universitas Malahayati, 2024)
ABSTRACT Genetic disorders are diseases caused by changes (mutations) in certain genes. This condition can be passed from parents to children, or occur randomly due to exposure to certain factors. Genetic diseases are caused by a number of factors, including defects in the mother's or father's genes, excessive abortion, a lack of blood cells, and a low white blood cell count. For premature or adolescent life development, early detection of genetic diseases is essential. Although it is difficult to predict genetic disorders in advance, these predictions are very important because the progress of a person's life depends on it. This scoping review focused on articles published in English from 1984 to 2022. The review included interventions related to calculating the inheritance patterns of genetic diseases and outcomes associated with these patterns. Encompassing randomized controlled trials, quasi-experimental studies, and cross-sectional research, the inclusion criteria excluded literature reviews, systematic reviews, and other scoping reviews. The review was conducted across four databases included PubMed, Scopus, ProQuest, and ScienceDirect, with critical appraisal conducted using the Joanna Briggs Institute's Critical Appraisal Checklist. Upon meeting the inclusion criteria, seven cross-sectional studies and quasi-experiments were identified. The review of intervention methods for calculating genetic diseases revealed outcomes associated with the inheritance patterns of genetic diseases. The intervention method for calculating genetic diseases has demonstrated its effectiveness in determining the inheritance patterns passed from parents to their children. This information is crucial for devising appropriate treatment plans for individuals affected by genetic diseases. Keywords: Genetic Counseling, Genetic Risk, Inheritance Pattern, Risk Calculation